Reminder Penerapan Protokol Kesehatan Pada Anak Sekolah Menjelang Libur Sekolah - Harahap, Yanna Wari; Pebrianhy, Lola; Listi, Silvia Yolandi; Harahap, Ardansyah; Harahap, Reni Ashari (Universitas Aufa Royhan Di Kota Padangsidipuan, 2020)
Covid-19 transmission does not look at gender, age or economy. Starting from children to adults can be infected. The transmission of the spread of the disease which is not known for sure when it will end makes us have to continue to care about education. Given the approaching school holiday period, it is necessary to resubmit health protocol material for students to remain vigilant about the transmission of Covid-19. Community service was carried out by lecturing methods using posters and videos to simulate health protocols. The results of community service increase the willingness and ability of students in implementing health protocols. With a reminder that the implementation of health protocols before school holidays can prevent the transmission of Covid-19 to school children in particular.